1984
DOI: 10.1002/ana.410150729
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomographic study of affective disorders: Problems and strategies

Abstract: Because anatomical studies of psychiatric disorders in humans have been largely unsuccessful, and because pharmacological interventions in patients with mental illness can be analyzed by means of biochemical assay techniques, positron emission tomography (PET) provides an exciting new means to study mental illness. Using fluorine-18-labeled fluorodeoxyglucose and PET to measure local cerebral glucose utilization, the investigators examined patients with affective disorders and normal age-matched controls. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(18 citation statements)
references
References 28 publications
1
16
0
1
Order By: Relevance
“…However, frontal and temporal glucose hypometabolism has been observed in major depression and in depression associated with other neurological diseases, using positron emission tomography. 29 - 30 In primary depression some authors found metabolic abnormalities involving both frontal and temporal cortices, 31 whereas others described glucose hypometabolism in either temporal 32 or frontal cortices. These previous observations, combined with the results of our study, suggest that interruption of pathways linking specific mesial temporal lobe regions may underlie depressive phenomenology.…”
Section: Discussionmentioning
confidence: 99%
“…However, frontal and temporal glucose hypometabolism has been observed in major depression and in depression associated with other neurological diseases, using positron emission tomography. 29 - 30 In primary depression some authors found metabolic abnormalities involving both frontal and temporal cortices, 31 whereas others described glucose hypometabolism in either temporal 32 or frontal cortices. These previous observations, combined with the results of our study, suggest that interruption of pathways linking specific mesial temporal lobe regions may underlie depressive phenomenology.…”
Section: Discussionmentioning
confidence: 99%
“…depressions are severe illnesses that may afflict 2% to 4% of the general population at any time1"2 and 4% to7% ofthe general population over the course of a lifetime.3 In addition to the nonspecific, subjective experience of unhappiness, these medical depressions are characterized by and distinguished from ordinary sadness or demoralization by substantial disturbances of sleep, appetite, sexual function, cognition, and (of most concern) suicidal behavior.4 Further¬ more, the natural course of depressive mood disorders is one of alternations between states of illness and overt health,5 occa¬ sionally to the point of rapid, clocklike cycling of mood with little relation to external events.6,7 Besides occurring as primary affective disorders, with or without episodes ofmania ("bipolar" and "unipolar" depressions,6,8 respectively), the symptoms of major depression are known to complicate other psychiatric disorders as "secondary" disturbances-notably in obsessive-compulsive disorder (OCD) 21.8 ±6.6 (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32) 30.5 ±7.0 (20-43) 43±10 (33-61) OCD-no major depression 14 33.8±10.6 9.3±4.1 (2-16) 29 Bipolar Manic-Phase Subjects.-There were two women and four men, none ofwhom were included in the bipolar depressed-phase group described above. All but one had previous episodes of severe depression.…”
Section: Majormentioning
confidence: 99%
“…Recently, positron emission tomography (PET) has been j applied to the brain, and can image nontumor CNS diseases [1][2][3][4][5][6][7][8] and brain tumors [9][10][11][12][13] from hemodynamic and met abolic points of view using various tracers including recep-1 tors. In clinical practice, the 18F-fluorodeoxyglucose (FDG)-.…”
mentioning
confidence: 99%